The economic burden of inpatient paediatric care in Kenya: household and provider costs for treatment of pneumonia, malaria and meningitis - Ayieko, P; Akumu, A; Griffiths, U; English, M (BioMed Central, 2009)
Background: Knowledge of treatment cost is essential in assessing cost effectiveness in healthcare. Evidence of the potential impact of implementing available interventions against childhood illnesses in developing countries challenges us to define the costs of treating these diseases. The purpose of this study is to describe the total costs associated with treatment of pneumonia, malaria and meningitis in children less than five years in seven Kenyan hospitals. Methods: Patient resource use data were obtained from largely prospective evaluation of medical records and household expenditure during illness was collected from interviews with caretakers. The estimates for costs per bed day were based on published data. A sensitivity analysis was conducted using WHO-CHOICE values for costs per bed day. Results: Treatment costs for 572 children (pneumonia = 205, malaria = 211, meningitis = 102 and mixed diagnoses = 54) and household expenditure for 390 households were analysed. From the provider perspective the mean cost per admission at the national hospital was US $95.58 for malaria, US $177.14 for pneumonia and US $284.64 for meningitis. In the public regional or district hospitals the mean cost per child treated ranged from US $47.19 to US $81.84 for malaria and US $56.06 to US $99.26 for pneumonia. The corresponding treatment costs in the mission hospitals were between US $43.23 to US $88.18 for malaria and US $43.36 to US $142.22 for pneumonia. Meningitis was treated for US $189.41 at the regional hospital and US $201.59 at one mission hospital. The total treatment cost estimates were sensitive to changes in the source of bed day costs. The median treatment related household payments within quintiles defined by total household expenditure differed by type of facility visited. Public hospitals recovered up to 40% of provider costs through user charges while mission facilities recovered 44% to 100% of costs. Conclusion: Treatments cost for inpatient malaria, pneumonia and meningitis vary by facility type, with mission and tertiary referral facilities being more expensive compared to primary referral. Households of sick children contribute significantly towards provider cost through payment of user fees. These findings could be used in cost effectiveness analysis of health interventions.